Technologies for the high seas: meeting the climate challenge. Issue 4 (4th July 2014) - Gilbert, Paul; Bows-Larkin, Alice; Mander, Sarah; Walsh, Conor
Background: Progress toward decarbonizing shipping has been slow compared with other sectors. To explore the scope for an urgent step-change cut in CO2, this paper presents results from a participatory technology roadmapping exercise.Results: Combining existing incremental and novel technologies with slow-steaming can deliver reductions in CO2 of over 50% even in the short term for existing ships. However, roadmaps for three vessel types illustrate barriers to change including the sector's complexity, infrastructure lock-in and a need for tailored market and vessel-specific roadmaps to support decision-making.Conclusions: Through technology and engineering, the outlook for the shipping sector to significantly cut its CO2 emissions, even in the short term, is promising. Nevertheless, the scale of change requires support to demonstrate how the long-term low-carbon vision offers enough benefit to overcome necessary short-term investment.